MDMA-Assisted Psychotherapy for Treatment of Posttraumatic Stress Disorder: A Systematic Review With Meta-Analysis - Smith, Kimberly W; Sicignano, Dakota J; Hernandez, Adrian V; White, C Michael (Journal of clinical pharmacology, 2022)
This article discusses current literature on the use of 3,4-methylenedioxymethamphetamine (MDMA)-assisted psychotherapy in the treatment of posttraumatic stress disorder (PTSD). MDMA, the intended active ingredient in illicit Ecstasy or Molly products, is a psychedelic that causes an elevated mood, feeling of bonding, and increased energy. In MDMA-assisted psychotherapy, patients are subjected to 2 or 3 multihour sessions of therapy with a team of psychiatrists. The dosing of MDMA is used to allow the therapist to probe the underlying trauma without causing emotional distress. The use of MDMA-assisted psychotherapy treatment reduced patient's Clinician-Administered PTSD Scale (CAPS) scores from baseline more than control psychotherapy (-22.03; 95%CI, -38.53 to -5.52) but with high statistical heterogeneity. MDMA-assisted psychotherapy enhanced the achievement of clinically significant reductions in CAPS scores (relative risk, 3.65; 95%CI, 2.39-5.57) and CAPS score reductions sufficient to no longer meet the definition of PTSD (relative risk, 2.10; 95%CI, 1.37-3.21) with no detected statistical heterogeneity. While therapy was generally safe and well tolerated, bruxism, anxiety, jitteriness, headache, and nausea are commonly reported. While MDMA-assisted psychotherapy has been shown to be an effective therapy for patients with PTSD with a reasonable safety profile, use of unregulated MDMA or use in the absence of a strongly controlled psychotherapeutic environment has considerable risks.